Pulmonary vein stenosis complicating radiofrequency catheter ablation for atrial fibrillation: A literature review. (August 2016) - Edriss, Hawa; Denega, Tatiana; Test, Victor; Nugent, Kenneth
Abstract: Radiofrequency catheter ablation has become a widely used intervention in the treatment of atrial fibrillation. Pulmonary vein stenosis (PVS) is one of the most serious complications associated with this procedure; the degree of stenosis ranges from mild (<50%) to complete venous occlusion. The natural history of PVS and the risk of progression of existing PVS are uncertain. Symptomatic and/or severe PVS is a serious medical problem and can be easily misdiagnosed since it is an uncommon and relatively new medical problem, often has low clinical suspicion among clinicians, and has a non-specific presentation that mimics other more common respiratory or cardiac diseases. The estimated incidence varies in literature reports from 0% to 42% of ablation procedures, depending on technical aspects of the procedure and operator skill. Most patients with significant PVS remain asymptomatic or have few symptoms. Symptomatic patients usually present with dyspnea, chest pain, or hemoptysis and are usually treated with balloon angioplasty and/or stent placement. Little is known about the long term effect of PV stenosis/occlusion on the pulmonary circulation and the development of pulmonary hypertension. Evolving technology may reduce the frequency of this complication, but long term studies are needed to understand the effect of therapeutic atrial injury and adverse outcomes. This review summarizes the current literature and outlines an approach to the evaluation and management of these patients. Highlights: Radiofrequency catheters use heat to create blocks around the pulmonary veins to prevent transmission of ectopic beets into the left atrium. Damage to the pulmonary veins can cause stenosis. Symptoms depend on the number of stenotic veins and the degree of stenosis. These patients have nonspecific signs and symptoms causing delayed diagnosis. Treatment options include venoplasty with or without stents.